Monoclonal Antibody Against Prolactin Receptor: A Randomized Placebo-Controlled Study Evaluating Safety, Tolerability, and Pharmacokinetics of Repeated Subcutaneous Administrations in Postmenopausal Women. (April 2019) - Nave, Rüdiger; Jodl, Stefan; Hoffmann, Anja; Gashaw, Isabella; Zollmann, Frank; Berse, Matthias; Höchel, Joachim; Krätzschmar, Jörn; Rohde, Beate
BAY 1158061 is a potent monoclonal prolactin (PRL) receptor antibody, blocking PRL receptor (PRLR)-mediated signaling in a noncompetitive manner, which was tested in a randomized, placebo-controlled multiple dose study in postmenopausal women. The objective was to investigate safety, tolerability, pharmacokinetic characteristics, and effects of BAY 1158061 on serum PRL level. The study consisted of 4 parallel groups receiving up to 3 subcutaneous (sc) administrations of BAY 1158061 or placebo in 2 different dosing regimens. Twenty-nine healthy postmenopausal women were randomized and treated with BAY 1158061 or placebo: 30 mg at 14-day interval (7 participants), 60 mg at 28-day interval (8 participants), 90 mg at 14-day interval (7 participants), and placebo (7 participants). To keep the blinding, all randomized participants received sc injections biweekly (14-day interval) on 3 occasions in the lower abdomen. The PRLR antibody showed a favorable safety and tolerability profile in postmenopausal women with no distinct differences in occurrence of adverse events in BAY 1158061 or placebo-treated participants. BAY 1158061 displayed low immunogenicity with low titers of antidrug antibodies and absence of neutralizing antidrug antibodies. Pharmacokinetics were characterized by slow absorption after sc administration with median peak plasma concentrations 7 to 11 days after first dose and about 2-fold accumulation after repeated dosing every 2 weeks. The apparent mean elimination half-life was 9 to 16 days. The PRL concentration–time profiles over 24 hours showed no differences between verum- and placebo-treated participants. Based on the data obtained, BAY 1158061 is considered a good candidate for further development in endometriosis or other PRL-mediated disease conditions.